HOW WOMEN LEAD PODCAST SERIES: FEMINIST MEDIA FRAMING IN CHALLENGING SYMBOLIC ANNIHILATION OF INDONESIAN WOMEN LEADERSHIP - Saputri, Gisa Maya (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2021)
The media presents gender stereotyping through its journalism works on a daily basis. This media framing could shape consumers’ beliefs and values. Women become the objects of media stereotyping since they are omitted from the discourse, condemned for the traditional gender role, and trivialized for being dependent. The rise of alternative media, including feminist media, challenges this situation. Magdalene, as one of the feminist media, releases a project of ‘How Women Lead’ podcast series. These podcast series are highlighted as the object to analyze how feminist media framing challenges the symbolic annihilation of women leaders. This paper intends to explore the framing of Indonesian women leaders in feminist media and to elaborate on the ways this feminist media challenges symbolic annihilation. The concept of symbolic annihilation in mass media by Tuchman (2000) becomes the basis of analysis. She classifies this concept into three categories; omission, condemnation, and trivialization. By employing Critical Discourse Analysis (CDA), this paper focuses on the power held by media for shaping people’s ideology through interpretation and explanation. The result proves that Magdalene through the ‘How Women Lead’ podcast series could promote inclusivity, opportunity, and independence as the main notions to challenge symbolic annihilation, particularly for women leaders.